Fabrication Of Gallium Nitride Nanowires Via Chemical Vapour Deposition - Low, Li Li (2012)
In this project, works are focusing on the investigation of the growth and characterization of GaN nanowires synthesized by Ni-catalyzed chemical vapour deposition under various experimental parameters including gallium source and substrate position, growth temperature, ammonia flow rate and reaction period. The comparative studies of the influence of these parameters on the morphological, structural and optical characteristics of the synthesized GaN were carried out in this project. The morphology of the synthesized GaN low dimensional wires was dependent on the position of Ga precursor and substrates. The position of Ga precursor and substrates was found to be able to affect the degree of supersaturation of gaseous reactants, which is essential in the growth of GaN wires by vapour-liquid-solid mechanism. Thus two different dimensional aspects of GaN micro- and nanowires were synthesized in this parameter study. The study of growth temperature revealed that 950ºC was the optimal growth temperature for synthesizing uniform, straight and smooth morphology of GaN nanowires with good elemental composition. On the other hand, the morphology and growth mechanism of GaN nanowires were dependent on NH3 flow rate. It was found that straight GaN nanowires were synthesized under low NH3 gas flow rate via vapour-liquid-solid mechanism whereas vermicular-like nanowires were synthesized under high NH3 gas flow rate via the vapour-solid mechanism. Additionally, the study of reaction period revealed that the synthesized GaN nanowires showing a uniform and straight morphology in the early growth process and subsequently transforming to vermicular-shape of nanowires with the increase of reaction period.